Modelling titania formation at typical industrial process conditions: Effect of surface shielding and surface energy on relevant growth mechanisms - Artelt, Christian; Schmid, Hans-Joachim; Peukert, Wolfgang (Chemical Engineering Science, 2006)
This work investigates the effects of reduced accessible surface area of aggregate particles and of surface energy on relevant particle formation and growth mechanisms during titania formation from the vapour phase at industrial process conditions. Growth due to surface reaction and due to condensation is related to the fraction of the surface area that is exposed to the collision with single molecules. Surface shielding is found to hamper surface reaction and condensation once fractal aggregates start to form. It leads to significantly retarded precursor consumption and produces aggregate particles, which consist of more, but smaller primary particles. Surface energy data are varied within a range as proposed by available literature data. Moderate and high surface energy values result in a thermodynamic barrier to the formation of new particles and are shown to reduce the formation of seed particles by several orders of magnitude. This leads to the formation of aggregate particles which consist of a rather small number of primary particles and mainly grow by surface reaction. The primary contribution of condensation to growth of individual primary particles is shown to be very little. However, condensation should not be neglected as it has a strong impact on particle formation rates and hence on product characteristics such as the number of primary particles and primary particle siz
Keywords: Surface energy; Surface shielding; Nanoparticles; Population balance; Titania; Condensation; Aerosol process simulations